Correlation of Nitrite Oxide with Severity and Survival Rate of Sepsis Patients - Sotianingsih, Sotianingsih; Mulyono, Budi; Dahesihdewi, Andaru; Halim, Samsirun; Syauqi, Ahmad (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
The objective of this research was to determine the correlation between Nitric Oxide (NO) levels with the severity ofsepsis, to describe the kinetics of NO levels, and to evaluate it in predicting mortality. This research was a longitudinal cohortobservational analytical study. The variables were serum NO levels and SOFA scores, which were serially evaluated. Thecorrelation test and difference test were used for statistical analysis. The survivor and the non-survivor group consisted of 14(41.18%) and 20 (58.82%) patients, respectively. There was a correlation between serum NO levels and the SOFA score at the24-hour observation (r=0.403; p=0.041). Non-parametric Mann-Whitney test showed that there was no kinetics of NOth levels at 0, 24, 72, and 144-hour observation (p-values =0.897 and 0.703, respectively). NO levels > 111,16 μmol/L at the 24hour could predict the risk of death with hazard ratio 4.7 compared to NO levels < 111,16 μmol/L. The survival rate ofpatients with serum NO levels <111,16 μmol/L and > 111,16 μmol/L was 83.3% and 37.5%, respectively. There was acorrelation between serum NO levels and SOFA scores at the 24-hour observation. However, there was no kinetics of NOlevels at serial evaluations. Nitric oxide levels with a cut-off of 111,16 μmol/L at 24 hours could predict the survival of septicth patients. Utilization of serum NO level at 24 hour can be used to evaluate the severity of septic patients and aggressivemanagement if there is an increase in serum NO levels > 111,16 μmol/L at 24 hours.